(untitled) (Performance, Religion, and Spirituality, 2017)
This article analyzes the antitheatrical sermons produced under the bishop of Québec, Jean-Baptiste de la Croix de Chevrières de Saint-Vallier, in response to a rumored performance of Molière’s Tartuffe in 1694. It makes the case that the performance of these sermons constituted a form of cultural protest in an early modern sense in that Saint-Vallier saw himself as a defender of the ideal social and religious order he envisioned for New France and drew on the same conservative tropes common to agents of pre-Revolutionary social unrest. Although France already had a long antitheatrical tradition by the end of the seventeenth century, theatrical performance proved particularly contentious in New France given that the colony lacked a printing press, making performance an essential medium for the transmission of information, or publication. Publication, the article argues, is also a useful way to understand the imperative to make devotion manifest or visible in Counter-Reformation Catholicism, which the sermons present plays as disrupting. The article concludes that as cultural protest, the sermons succeeded. They helped suppress theatrical activity in New France for more than a century. However, when evaluated in relation to Saint-Vallier’s spiritual objectives, his sermonic protests against the theater failed. By emphasizing the outer forms of devotion, Saint-Vallier turned theatricality into the enemy within.